The Possibilities of a priori Reasoning: Applying the Praxeological Method to Political Analysis - Marcinkevičius, Leonardas (Politologija, 2025)
This article explores the potential of applying a priori deductive reasoning within political science. Contemporary social science methodology relies heavily on empirical research, which is often insufficient for uncovering the universal structure of human action. The article argues that praxeology, the method developed by Ludwig von Mises and grounded in the axiom “man acts”, can provide a suitable epistemological foundation for political science. It emphasizes that pure reason can serve as a valid source of knowledge for certain social phenomena, since all social sciences may begin with analysis of the axiom of human action.To substantiate this argument, the article draws on Immanuel Kant’s account of a priori reasoning, the distinction between historical and philosophical sciences, and the principle of methodological dualism. It maintains that, when combined with a value-neutral definition of the state and politics, praxeology allows political science to be reconceptualized as a branch of the broader science of human action. The article concludes that such an approach opens the possibility of reinterpreting the unique functions and limits of the state, as well as reflecting on the normative dimension of politics.